Analysis of the Transformation of National Education Standards Policy in Improving the Quality of Islamic Religious Education in Indonesia - Eti Sapitri; Helmiati Helmiati; Hariza Hasyim (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to analyze the transformation of National Education Standards (SNP) policies in Indonesia and their implications for the quality of Islamic Religious Education (PAI). Previous studies have addressed SNP and PAI separately; thus, this study offers an integrative analysis bridging both domains. Employing a qualitative descriptive-analytical library research approach, this study analyzed 34 scientific sources retrieved systematically from Google Scholar, Scopus, and Garuda (SINTA/BRIN) using inclusion and exclusion criteria. The findings reveal that SNP transformation from Government Regulation No. 19 of 2005 to No. 57 of 2021 in conjunction with No. 4 of 2022 reflects a paradigm shift from compliance-based toward continuous quality assurance. However, its implementation in PAI faces three main challenges: cognitive and administrative dominance, knowledge dichotomy in the curriculum, and limitations in assessing students' spiritual dimensions. This study proposes a conceptual integration model of SNP–PAI through reinterpretation of the eight national education standards based on Islamic values, emphasizing tauhidization, holistic-integrative education, and transformative learning toward the formation of insan kamil.